الوحدة العربية في السياسة الخارجية الليبية من ١٩٦٩-١٩٩٩: The Arab unity in Libyan foreign policy 1969-1999 - Ahmed Abushowaisha, Ruqayah Abdalhadi; Abdelsalam, El Fatih Abdullahi (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص تبرز أهمية هذه الدراسة في تسليط الضوء على مفهوم الوحدة العربية كمبدأ أساسي في السياسة الخارجية الليبية خلال الفترة من 1969 إلى 1999. حيث مثلت قضية الوحدة العربية الهدف المركزي للسياسة الخارجية الليبية خلال تلك الفترة، وهذا يعتبر إشكالية هذه الدراسة أيضاً. الهدف الأساسي لهذه الدراسة يكمن في دراسة الوحدة العربية كهدف رئيس للسياسة الخارجية الليبية خلال الفترة موضوع الدراسة، والمشاريع الوحدوية العديدة على مدى ثلاثة عقود من خلال تحليل الوثائق. اعتمدت الدراسة المنهج التاريخي وذلك بتتبع وتحليل تلك الوثائق في إطارها التاريخي. كما اعتمدت الدراسة المنهج التحليلي في مقاربتها لتلك الوثائق بهدف التوصل لأهمية الوحدة العربية في السياسة الخارجية الليبية. تؤكد هذه الدراسة أن الهدف من الوحدة العربية تم تحديده أساسًا على عدة عوامل سياسية واقتصادية وأيديولوجية. بالإضافة إلى ذلك، تظهر الدراسة أن جميع محاولات تحقيق الوحدة العربية اتسمت بالتسرع، وعدم التخطيط العقلاني، وافتقارها إلى رؤية واضحة ودقيقة للسياسة الخارجية الليبية. Abstract This study highlights the concept of Arab unity as a cardinal principle in Libyan foreign policy during the period 1969-1999 of Gaddafi epoch. During this period Arab unity, which is also the essential issue of this study, became the core goal for Libyan foreign relations. The major objective of this study is to analyse Arab Unity Documents during that period to determine the orientation of Libyan foreign policy towards the unity issue. The study has used the historical approach to analyse the unity documents in their historical context. In addition to this, the study has used the analytical method in order to identify and analyse all unity attempts of Libyan foreign policy. This study underscores that the objective of Arab unity was mainly determined based on political, economic and ideological factors. In addition, the study shows that all attempts to achieve Arab unity were characterized by haste and lack of rational planning as well as lack of clear and careful vision in Libyan foreign policy.